2021
DOI: 10.3390/nu13020703
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Function in Patients with Inflammatory Bowel Disease (IBD) Is Associated with Their Body Mass Index and Polymorphism in the Odor Binding-Protein (OBPIIa) Gene

Abstract: Smell strongly contributes to food choice and intake, influencing energy balance and body weight; its reduction or loss has been related to malnutrition problems. Some patients with inflammatory bowel disease (IBD), mainly Crohn’s disease (CD) and ulcerative colitis (UC), are underweight, while others are overweight. Some studies suggest that changes in eating habits could be linked to specific disorders of the olfactory functions. We assessed the olfactory performance in 199 subjects (healthy control (HC) n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 95 publications
1
14
0
Order By: Relevance
“…Finally, studying the loss of smell and taste due to COVID-19 and its relationship with impairments in the peripheral and central nervous system offers the opportunity to identify other possible mechanisms involved in dysregulated eating behaviour in obesity. Already, some studies, outside the context of the pandemic, have suggested that defective smell and taste may predispose to obesity, providing a tantalizing clue regarding the potential association of altered smell with obesity in general population [ 70 ], by representing a new potential target for possible anti-obesity treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, studying the loss of smell and taste due to COVID-19 and its relationship with impairments in the peripheral and central nervous system offers the opportunity to identify other possible mechanisms involved in dysregulated eating behaviour in obesity. Already, some studies, outside the context of the pandemic, have suggested that defective smell and taste may predispose to obesity, providing a tantalizing clue regarding the potential association of altered smell with obesity in general population [ 70 ], by representing a new potential target for possible anti-obesity treatments.…”
Section: Discussionmentioning
confidence: 99%
“…This variability can be due to both environmental and genetic factors [ 35 , 37 , 38 , 39 , 40 ]. Olfactory deficits are also associated with several chronic diseases such as hypertension, neurodegenerative diseases (Parkinson’s, Alzheimer’s), depression, autoimmune/inflammatory diseases and obesity [ 41 , 42 , 43 , 44 , 45 , 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…In agreement, not only exercise activities but also higher levels of non-exercise activity were found to be associated with cognitive abilities in aged adults (Buchman et al, 2012 ). Second, exercise reduces the risk factors for certain diseases such as diabetes, hypertension, metabolic disorders, depression, obesity, and inflammatory diseases, which converge to cause brain dysfunction and neurodegeneration (Franco et al, 2005 ; Cotman et al, 2007 ; Buchman et al, 2012 ; Hamer et al, 2012 ) and are pathologies associated with a reduction in the olfactory function (Graves et al, 1999 ; Ross et al, 2008 ; Wilson et al, 2009 ; Perricone et al, 2013 ; Croy et al, 2014a ; Pinto et al, 2014 ; Kim et al, 2019 ; Sollai et al, 2021 ); this may explain why among active older adults we observed both a higher number of normosmic subjects and higher olfactory scores.…”
Section: Discussionmentioning
confidence: 99%
“…Humans show a great inter-individual variability in their olfactory perception, both of complex odors and single molecules, due to environmental and genetic factors (Keller et al, 2007 ; Menashe et al, 2007 ; Calderón-Garcidueñas et al, 2010 ; Sorokowska et al, 2013 ; Sollai et al, 2019 , 2020 ; Melis et al, 2021 ). In addition to chronic diseases such as neurodegenerative, inflammatory/immune, cardiovascular, metabolic, depressive, renal, nasal, and hepatic ones (Graves et al, 1999 ; Larsson et al, 1999 ; Seiberling and Conley, 2004 ; Boesveldt et al, 2008 ; Ross et al, 2008 ; Doty, 2009 ; Wilson et al, 2009 ; Steinbach et al, 2011 ; Palouzier-Paulignan et al, 2012 ; Perricone et al, 2013 ; Attems et al, 2014 ; Croy et al, 2014b ; Doty and Kamath, 2014 ; Makizako et al, 2014 ; Stuck and Hummel, 2015 ; Sollai et al, 2021 ), one of the factors that mainly affects the olfactory function is the natural aging process (Doty et al, 1984 ; Cain and Stevens, 1989 ; Min et al, 2021 ) and the progressive sensory deterioration with age (Schubert et al, 2017 ). Population-based studies of olfactory loss indicate that the maximum olfactory performance occurs between the 3rd and the 5th decade and that a reduced olfactory function is very common in elderly populations, affecting more than 50% of individuals aged between 65 and 80 years and 62–80% of the elderly over 80 years (Doty et al, 1984 ; Attems et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%